PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMK BUDI MULIA TANGERANG - Nachrowi Iman Santoso (MIX: JURNAL ILMIAH MANAJEMEN, 2013)
Abstract: This research is conducted to analyze andreveal the influence of PrincipalLeadership and work motivation on the Performance of teachers in SMK Budi MuliaTangerang. Principal's leadership role in the process of moving, influencing andguiding others in order to achieve organizational goals is the role to be performed aswell as the leadership of the principal motivation influences from within and outsidemotivation. Research methodology used was a survey method is descriptive analytic.Techniques used in the determination of the sample is saturated sampling (census) inwhich all members of the population sampled. The results of the study showed theinfluence of the principal's leadership and work motivation on the performance ofteachers in vocational high school Budi Mulia Tangerang. The influence of principalleadership effects on teacher performance, especially on intellectual developmentdimension to the dimensions of work ability and initiative, inspiring dimensions to thedimensions of the initiative, the influence of ideal dimensions to the dimensions ofwork ability and discipline, each has a strong-enough relationship while on workmotivation has a strong relationship, particularly on the dimensions of the inside of thedimensions of initiative..Keywords: principalleadership, work motivation, teacherperformance.